Unveiling Profitability Drivers in ASEAN Islamic Banking: A Panel Data Analysis - Muttaqin, Ibnu (Faculty of Economics UIN Maulana Malik Ibrahim Malang, 2025)
This study examines the determinants of profitability in Islamic banking across five Association of Southeast Asian Nations (ASEAN) countries, including Indonesia, Malaysia, Brunei Darussalam, the Philippines, and Thailand, from 2018 to 2022. Using panel data regression, the study examines both Return on Assets (ROA) and Return on Equity (ROE) as measures of profitability. The population consists of all Islamic banks operating in the ASEAN region. Through purposive sampling, the study selected 127 data observations from banks with complete and consistent financial data. The models were estimated using Fixed Effect Models (FEM) with robust standard errors to correct for heteroskedasticity. The findings reveal that efficiency, Market Concentration (HHI), and inflation consistently have a positive and significant impact on both ROA and ROE. Financing to Deposit Ratio (FDR) positively affects only ROE, while Gross Domestic Product (GDP) unexpectedly shows a negative relationship with ROE. Other variables such as bank size, market share, and the Sharia Supervisory Board (SSB) are statistically insignificant. These results suggest that internal efficiency and market structure are more critical to Islamic bank profitability than macroeconomic scale or governance mechanisms. This study fills the empirical gap in the literature by offering comparative insight into Islamic bank performance across the ASEAN region.